2006
DOI: 10.1002/pssa.200521483
|View full text |Cite
|
Sign up to set email alerts
|

Thermal development of microstructure and precipitation effects in Mg–10wt%Gd alloy

Abstract: Thermal effects on the microstructure and precipitation in Mg -10wt%Gd alloy were studied in this work. The role of lattice defects was investigated using positron annihilation spectroscopy. Studies of defects by positron annihilation were combined with X-ray diffraction and microhardness measurements. Vacancies bound to Gd atoms were found in the homogenised sample quenched down to room temperature. Subsequently, clustering of Gd atoms takes place with increasing temperature. The Gd-rich clusters represent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The lifetime  b = 220.0(1) ps obtained in this way is consistent with the lifetime observed in the non-burnished sample. The lifetime in defects  2 = 281(7) ps is intermediate between lifetimes characteristic for dislocation (~255 ps) and monovacancy (~300 ps) in Mg [15,17,18]. This suggests that both these defects exist in the samples.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The lifetime  b = 220.0(1) ps obtained in this way is consistent with the lifetime observed in the non-burnished sample. The lifetime in defects  2 = 281(7) ps is intermediate between lifetimes characteristic for dislocation (~255 ps) and monovacancy (~300 ps) in Mg [15,17,18]. This suggests that both these defects exist in the samples.…”
Section: Resultsmentioning
confidence: 92%
“…There are two ways of explaining the lack of ) [11] or, in contrast, all positrons are trapped in defects. The lifetime expected for the Mg bulk value was found to be between 218 ps and 225 ps [10,[15][16][17][18]. Thus, the lifetime observed in the AZ91HP alloy would rather point to the fi rst explanation.…”
Section: Resultsmentioning
confidence: 96%
“…The numerical processing of lifetime spectra obtained from specimens after different number of ECAP passes showed that they can be well fitted by two exponential components. The shorter component with the lifetime τ 1 < τ B = 225 ps [13], where τ B represents the lifetime of free positrons in pure Mg, corresponds to the lifetime of free positrons in AZ31 while the longer component τ 2 ≈ 260 ps represents positrons trapped at dislocations [14]. As no other components were found in PAS lifetime spectra one can conclude that the dislocations are the only lattice defects present in specimen after ECAP.…”
Section: Dislocation Densitymentioning
confidence: 85%
“…The spectrometer exhibits excellent timing resolution of 145 ps ͑full width at half maximum 22 Na͒. The PL spectra, which always contained at least 10 7 positron annihilation events, were decomposed using a least square fitting program LT Coincidence Doppler broadening ͑CDB͒ studies were carried out using a spectrometer 21 equipped with two high purity Ge detectors. The energy resolution of the CDB spectrometer is ͑1.02Ϯ 0.01͒ keV at 511 keV.…”
Section: B Pasmentioning
confidence: 99%